2022
DOI: 10.3390/inventions7010009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Plastic Strain Distributions and Mechanical Behaviour of a Tube under Bending

Abstract: Tubular pipe structures have been used in various applications—domestic, aviation, marine, manufacturing and material testing. The applications of tubular pipes have been considered greatly in the installation of tubular pipes, marine risers and pipe bending. For the investigation of plastic strains and the mechanical behaviour of a tube under bending, considerations were made utilising an exponent model with assumptions on the plane strain. The bending moment, wall thickness effect, cross-sectional distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…As seen on Figure 10, there are different locations of the damages to the helical spring reinforcement, which the authors identified as "damage sites". Similar fatigue studies on helix reinforcement include composite cords [76], as micro-cracks are seen in the composite materials [87], meaning the helix damage observed here is novel. From Figure 10, it is evident that the stress profile along the…”
Section: Results Of Helix Localised Damagesupporting
confidence: 69%
See 1 more Smart Citation
“…As seen on Figure 10, there are different locations of the damages to the helical spring reinforcement, which the authors identified as "damage sites". Similar fatigue studies on helix reinforcement include composite cords [76], as micro-cracks are seen in the composite materials [87], meaning the helix damage observed here is novel. From Figure 10, it is evident that the stress profile along the…”
Section: Results Of Helix Localised Damagesupporting
confidence: 69%
“…The liner wrinkling is an indication that the liner material may be compromised, or that the metal-composite interface between the liner and the composite material is weakened. Even in bonded contacts, there is still a high prevalence of micro-strains [87] and micro-cracks [88]. Thus, there might be micro-cracks resulting from the liner wrinkling.…”
Section: Results Of Hose's Liner Wrinklingmentioning
confidence: 99%
“…For the local design of the reeling hose, ANSYS Structural version R2 2020 [83,84] and Simscale OpenFEA [47,85] were utilised. Both platforms were used to ascertain the different physics investigated on the loading conditions of the marine reeling hose to present results from both statics and dynamic behaviour of the hose.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Secondly, these multi-layered risers have similar behaviour to marine hoses in mechanical performance. They both exhibit some mechanical-related behaviours in terms of delamination, contacts, liner collapse, and fatigue [46][47][48][49][50][51]. In principle, these marine hoses are designed using both global and local designs [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the engineers are concerned with the challenges, concepts, awareness, utility, management of engineering facilities and development of new technologies [25] [26] [27] [28]. These technologies are used to develop construction materials like pipes and hoses [29] [30] [31] [32] as well as 3D-printed face shields [33] [34] [35].…”
Section: Introductionmentioning
confidence: 99%